The Development of a Centralized Platform for Finding Tutor - Faizil, Fe Puteri Salsabila (IRC, 2020)
Nowadays,students are having problem in having online classes due to limited access for learning material and assistance by friends or lecturers. Even the application of seeking tutors was established before, few problems still occur. The first problem is the existing applications offer limited features for the users such as the students are unable to find the nearby tutor. The second problem is students have time constraint to contact their lecturers because of there are many procedures to do in order forthem to have personal virtual meeting. The third problem is the existing learning material that students received from their lecturers sometimes are not sufficient. This leads to them to seek the reference on the internet which in result they must pay for it in order to download or view. Hence, the proposed system will be developed which can be an aid for the students and even the tutors to conduct the personal online class. This system will help them to search the tutors based on location and course or subject. Once they find a suitable tutor, they will be able to make a booking by sending a request that will be notified to the tutor by the admin. Besides that, students can give feedback and rating for the tutors right after the lecture session end. The rate will be recorded as a report for the admin to monitor the process.